2011
DOI: 10.1128/aac.00375-11
|View full text |Cite
|
Sign up to set email alerts
|

Meningeal Inflammation Increases Artemether Concentrations in Cerebrospinal Fluid in Papua New Guinean Children Treated with Intramuscular Artemether

Abstract: Although the artemisinin-associated neurotoxicity identified in vitro and in animal studies has not been confirmed clinically, only one adult study has measured cerebrospinal fluid (CSF) concentrations after administration of conventional doses. Potential artemisinin neurotoxicity could be serious in children, especially those with meningitis and, consequently, a compromised blood-brain barrier. We measured CSF/plasma artemether and dihydroartemisinin (DHA) concentrations in 32 Papua New Guinean children with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Only concentrations of Ն20 M caused measurable cytotoxic effects. It should be mentioned that neurotoxicity has been observed exclusively in animal studies with high artesunate concentrations and never in humans given the recommended doses (59).…”
Section: Discussionmentioning
confidence: 99%
“…Only concentrations of Ն20 M caused measurable cytotoxic effects. It should be mentioned that neurotoxicity has been observed exclusively in animal studies with high artesunate concentrations and never in humans given the recommended doses (59).…”
Section: Discussionmentioning
confidence: 99%
“…The concentration of ART in plasma was analyzed using liquid chromatography with mass spectrometry detection (LC-MS) based on an established assay for artemether (36). Stock solutions of ART and artemether (the internal standard) were prepared separately (1 g/liter in methanol) and were stored in the dark at Ϫ80°C.…”
Section: Methodsmentioning
confidence: 99%
“…There were 237 individual plasma DHA concentrations available for analysis, of which 43 (18.1%) were BLQ. As these represented a significant proportion of the data, a method previously described, namely, M3 (31), and successfully utilized in the PK analysis of antimalarial drugs (25,32) was employed. Initial modeling of the DHA data set demonstrated that a two-compartment model was not significantly better than a one-compartment model (⌬OFV ϭ Ϫ6.171, P ϭ 0.023, degrees of freedom [df] ϭ 2) and that the absorption phase was best de- scribed by a first-order absorption with a lag time.…”
Section: Safety and Tolerability (I) Adverse Events And Symptomsmentioning
confidence: 99%